Impact of Traumatic Brain Injury on Neurogenesis - Ngwenya, Laura B.; Danzer, Steve C. (Frontiers in Neuroscience, 2019)
New neurons are generated in the hippocampal dentate gyrus from early development through adulthood. Progenitor cells and immature granule cells in the subgranular zone (SGZ) are responsive to changes in their environment; and indeed, a large body of research indicates that neuronal interactions and the dentate gyrus milieu regulates granule cell proliferation, maturation and integration. Following traumatic brain injury (TBI), these interactions are dramatically altered. In addition to cell losses from injury and neurotransmitter dysfunction, patients often show electroencephalographic evidence of cortical spreading depolarizations and seizure activity after TBI. Furthermore, treatment for TBI often involves interventions that alter hippocampal function such as sedative medications, neuromodulating agents, and anti-epileptic drugs. Here, we review hippocampal changes after TBI and how they impact the coordinated process of granule cell adult neurogenesis. We also discuss clinical TBI treatments that have the potential to alter neurogenesis. A thorough understanding of the impact that TBI has on neurogenesis will ultimately be needed to begin to design novel therapeutics to promote recovery.